Relationships Between Perceived Usefulness and Fitness Wearable Technology User Adoption Mediated by Culture, Gender, and COVID-19: A Meta-Analysis - Shi, Lizhen; Huang, Xiaoling; Abbas, Safdar; Yang, Zong Qian; Huang, Li (Quality in Sport, 2022)
With COVID-19 raging and individuals exercising at home, the adoption of fitness wearable technology (FWT) that help people monitor their physical state has become a pressing matter. Here, we try to bridge the gap that no researcher has examined the link between perceived usefulness (PU) and FWT adoption by using meta-analysis to comprehend the detailed numerical values and moderating factors affecting the relationship. A total of 24 articles with 7180 re-pendants were investigated from January 1, 2015 to March 1, 2022 A.D, producing significant results as follows: (1) There is publication bias in relevant research, and sensitivity analysis suggests that PU influences FWT adoption positively; (2) Subgroup test and regression analysis suggested that cultural background, gender, and COVID-19 can deepen this relationship to varying degrees. More precisely, female (r=0.669) have a greater impact on FWT adoption than men (r=0.658). In addition, users in other countries (r=0.670) are more concerned about PU than Chinese users (r=0.658). Regression analysis showed that after the COVID-19 outbreak, the coefficient (r=0.762) of PU on FWT adoption increased significantly, indicating that people need FWT-assisted exercise to understand and maintain their own physical fitness. The research opens up new ideas for different governments and scholars to promote mass fitness and public health during the COVID-19, providing a reference for the scientific research and development of PU and marketing promotion of the related enterprises’ FWT.